Implementasi Equivalence Partitioning Testing Pada Fitur Booking dan Jadwal Website Praktik Gigi Mandiri drg. Susilawati (https://frontend-webklinik.vercel.app/) - Nasir, Muhammad; Halimi, Keysha Maulina; Putri, Tiara Ariyanto; Maryadi, Muhammad Rahmat; Pradipta, Rayhan Ananda Hafiz; Matouq, Hassan Nasrallah; Wicaksono, Aditya (Universitas Indraprasta PGRI Jakarta, 2025)
The advancement of information technology in the healthcare sector has driven the digitalization of services, including the management of reservations and schedules in dental practices. The Praktek Gigi Mandiri Website was developed to assist the dental clinic of drg. Susilawati in efficiently managing patient appointments through the Booking and Scheduling features. This study aims to test the functionality of these features using the Black Box Testing method with the Equivalence Partitioning technique, focusing on functional Testing without considering the internal structure of the system. Testing was conducted on several main scenarios, including viewing schedules, adding schedules, editing schedules, deleting schedules, and making reservations. The test results indicate that the Booking feature achieved a success rate of 50%, while the Scheduling feature reached 57.14%. Overall, the combined success rate of both features is 53.85%, showing that most functions operated as expected. However, some scenarios failed due to insufficient input validation and inadequate error handling. The limitation of this Testing lies in its focus on functionality without involving performance and security Testing. Therefore, further Testing is needed to ensure system stability and security before full implementation. Overall, the Praktek Gigi Mandiri Website has successfully performed its main functions, but further improvements are necessary to enhance system reliability and user experience.